Cyclization of PLP139-151 peptide reduces its encephalitogenic potential in experimental autoimmune encephalomyelitis. Issue 9 (15th May 2018) - Lourbopoulos, Athanasios; Matsoukas, Minos-Timotheos; Katsara, Maria; Deraos, George; Giannakopoulou, Aggeliki; Lagoudaki, Roza; Grigoriadis, Nikolaos; Matsoukas, John; Apostolopoulos, Vasso
Graphical abstract: Abstract: We report the novel synthesis of cyclic PLP139-151 (cPLP) and its application in SJL/J mice to study its encephalitogenic effects. Our results indicate that the cPLP analog is minimally encephalitogenic when administered to induce experimental autoimmune encephalomyelitis (low disease burden, minimal inflammatory, demyelinating and axonopathic pathology compared to its linear counterpart). Proliferation assays confirmed the low stimulatory potential of the cPLP compared to linPLP (2.5-fold lower proliferation) as well as inducing lower antibody responses. Molecular modeling showed a completely different TCR recognition profile of cPLP in regard to linPLP, where H 147 replaces W 144 and F 151 -K 150 replace H 147 as TCR contacts, which may explain the difference on each peptide's response.